The Influence of Islamic Celebrity Endorser, Islamic Brand Image and Product Quality through Price as Moderating Variable on The Purchase Decision of Wardah Cosmetic Products - Darmawati, Darmawati; Arum, Kanthi; Yuliani, Irma (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The emergence of the statement "Realize Inspiring Beauty" led to the use of Islamic celebrity endorsers who have characteristics, able to influence behavior (attitude). Islamic Brand Image becomes the most important factor in determining product quality, while price influences consumer views and is the most influential factor in the purchasing process. The purpose of this study is to determine the effect of Islamic Celebrity Endorser, Islamic Brand Image and product quality through price which is moderating variable on the purchasing decision of Wardah cosmetic products. This study used quantitative method. With a sample of 200 respondents from UIN SAMI and UMKT. The analytical method which used in this research was multiple linear regression analysis. The results of this study indicated that Islamic Celebrity Endorser had a significant positive effect on consumer decisions to buy Wardah cosmetic products. Islamic Brand Image had a significant positive effect on consumers' decisions to buy Wardah cosmetic products. Product quality had a significant positive effect on consumers' decisions to buy Wardah cosmetic products and prices were able to strengthen the variables of Islamic Celebrity Endorser, Islamic Brand Image and Product Quality on consumers' decisions to buy Wardah cosmetic products.